FUTURE MATHEMATICS AND INFORMATICS TO THEIR TEACHERS NETWORK TECHNOLOGIES SCIENCE TRAINING - Ziyoyev Sh (International Journal of Innovations in Engineering Research and Technology, 2022)
This in the article "Network technologies" science in learning in students modern information and communication technologies own professional in the activity conscious and critical point of view mean apply ability formation to the problem dedicated.